An amino-substituted 2-(2′-hydroxyphenyl)benzimidazole for the fluorescent detection of phosgene based on an ESIPT mechanism. Issue 18 (15th March 2021) - Li, Zi-Jie; Zhang, Wen-Jie; Bi, Wen-Zhu; Ma, Qiu-Juan; Feng, Su-Xiang; Chen, Xiao-Lan; Qu, Ling-Bo
Abstract : An easily prepared phosgene probe, 5′-amino-2-(2′-hydroxyphenyl)benzimidazole (P1 ), is designed and studied. Based on ESIPT mechanism, P1 exhibits ratiometric, sensitive and selective detection of phosgene both in solution and gas phase. Abstract : In this work, an ESIPT-based fluorescence probe, 5′-amino-2-(2′-hydroxyphenyl)benzimidazole (P1 ), was synthesized and explored for the ratiometric detection of phosgene. Compared to 2-(2′-hydroxyphenyl)benzimidazole (HBI), P1 exhibits high sensitivity (LoD = 5.3 nM) and selectivity toward phosgene with the introduction of the amine group. Furthermore, simple P1 loaded test papers are manufactured and display selective fluorescent detection of phosgene in the gas phase.